Designing the Surface and Underground Blasting Operations to Avoid Damage to Concrete Structures in Gotvand Olya Dam Using Genetic Algorithm - Bahadori, Moein (Geotechnical and geological engineering, 2022)
Ground vibration is one of the destructive effects of rock blasting. The prediction and control of the blast-induced ground vibrations are very important in mining and construction projects. Therefore, the maximum possible efficiency of the operation should be determined by considering the safety range. In this paper, to estimate the effect of surface and underground blast-induced ground vibration on concrete structures in the area of Gotvand Olya Dam, 30 and 14 records of 21 surface and 4 underground blasting operations (totally 44 data), respectively, were recorded using PG-2002 seismographs. The ground vibrations from the blasting operations were estimated using two empirical relationships with the accuracy of 0.93 and 0.88 for the surface and underground operations, respectively. With the help of a Genetic Algorithm (GA), the correlation of these relationships has increased to 0.96 and 0.9, respectively. Considering the elapsed time of concrete and using the U. S. Army Corps of Engineers standard, the allowable charge weight per delay was calculated for both operations for a hypothetical distance of 50 m. Based on the results of this study, the surface and underground blasting operations can be operated using Cordtex and Nonel systems, while the empirical relationships allow only the Nonel system with limited delay times or a limited number of blast holes. It is also recommended that, if possible, no blasting operations be carried out in the first 24 h of concreting. In case of exigency, the operation is scheduled in the first 7 h of concreting.